Al-Ghazali’s Contributions to Islamic Education - Hasnan, Hasnan; Eramahi, Eka (El-Rusyd, 2026)
As a thinker, Imam al-Ghazali has made significant intellectual contributions to the advancement of Islamic education. However, the application of al-Ghazali’s concepts has not yet been widely observed in Islamic educational institutions. The purpose of this paper is to examine the contribution of al-Ghazali’s thought to Islamic education. This paper focuses on three aspects: the first relates to ethics, the second to the curriculum, and the third to teaching methods. This research is descriptive qualitative in nature, employing content analysis. This involves examining and analyzing books, literature, magazines, notes, and reports related to the subject under study. The analysis revealed that al-Ghazali’s contributions to Islamic education are as follows: i) Ethics. According to al-Ghazali, good character (Akhlaq Mahmudah) is the fruit and ultimate goal of the entire educational process and the pursuit of knowledge. ii) Curriculum. Al-Ghazali views the curriculum not merely as a list of subjects, but as a roadmap for transforming the soul (tazkiyatun nafs) from blameworthy traits (akhlaq mazmumah) toward praiseworthy traits (akhlaq maḥmudah). iii) Teaching methods. According to al-Ghazali, the method of learning (tariqah al-ta’allum) cannot be separated from the goals of education, namely the purification of the soul (tazkiyatun nafs) and the attainment of ma’rifat of Allah.